Thibaq and Muqabalah in Surah Al-Mulk: A Stylistic Study of Semantic Contrast and Theological Persuasion - Nisa', Azzyra Sholikhatun; Muttakin, Khaerul (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2025)
Surah Al-Mulk articulates divine sovereignty, accountability, and inzār through a discourse that relies on patterned semantic contrast. This study examines how thibāq and muqābalah function stylistically in the surah to organize rhetorical meaning and reinforce theological emphasis. The analysis is grounded in classical balāghah, with particular attention to al-Sakkākī’s principle of muṭābaqat al-kalām li-muqtaḍā al-ḥāl in order to explain the fit between linguistic form and communicative context. Using qualitative textual research, the study identifies contrastive indicators through close reading and applies classical criteria to select relevant verses. The analysis focuses on thibāq in Q. 2, 13, 19, 22, and 30, and on muqābalah in Q. 6–9. Findings show that thibāq operates through direct oppositional pairings and contextual contrasts that sharpen moral differentiation and intensify theological focus at the level of individual verses. In Q. 6–9, muqābalah is realized mainly as muqābalah maʿnawiyyah, where punishment and denial are foregrounded while counter-meanings are prompted through semantic absence, fitting the inzār setting. The study argues that thibāq and muqābalah form a connected stylistic system that supports the surah’s persuasive direction through contrast, concision, and guided inference.